1991
DOI: 10.2307/1130815
|View full text |Cite
|
Sign up to set email alerts
|

Television and Families: What Do Young Children Watch with Their Parents?

Abstract: A sample of 271 3- and 5-year-olds and their families participated in a 2-year longitudinal study of television viewing patterns. 5 1-week diaries for all family members were collected at 6-month intervals. Programs were categorized as: (1) child informative, (2) child entertainment, (3) news and informative, (4) sports, (5) comedy, (6) drama, (7) action-adventure, and (8) variety-game. The majority of child programs were viewed without parents, while the majority of adult programs were watched with parents. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Coviewing with parents is more typical when children are watching programs parents want to view. 76 Given the high rates of violent content on TV, 77,78 it is likely that the child would be exposed to violent content while coviewing.…”
Section: Resultsmentioning
confidence: 99%
“…Coviewing with parents is more typical when children are watching programs parents want to view. 76 Given the high rates of violent content on TV, 77,78 it is likely that the child would be exposed to violent content while coviewing.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, whereas coviewing is often suggested as a strategy to mitigate the effects of television content, 4 studies have shown that children usually watch the shows that parents want to watch. 32,33 Future research should investigate the empirical question of whether any benefits of coviewing outweigh the risks associated with an increase in TVV that is related to coviewing. Specifically, more detailed measures of the quality of coviewing and decisions about the content of coviewed programming would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Single‐item assessment of media use does not provide contextual data (e.g., child viewed coverage with parents, child was online alone). Media use can be a family activity and viewing television may be the most frequent family activity (Timmer, Eccles, & O’Brien, 1985; St. Peters et al., 1991).…”
Section: Media‐based Contact With Actual Terrorist Attacksmentioning
confidence: 99%
“…Research has failed to investigate the important role of parents in reducing or increasing youth anxiety triggered by media presentations of terrorism possibilities. Media use can be a social activity (Kubey & Csikszentmihalyi, 1990; St. Peters et al., 1991; Timmer et al., 1985) and greater child television viewing has been associated with increased parent–child contact (Krosnick et al., 2003).…”
Section: Secondhand Terrorism: Media‐based Contact With the Possibilimentioning
confidence: 99%